昭和基地での生活水の確保 - 石沢, 賢二; イシザワ, ケンジ; 林原, 勝美; ハヤシバラ, カツミ; Ishizawa, Kenji; Hayashibara, Katsumi (2015)
P(論文) 日本南極地域観測隊は，第1次越冬隊以来，昭和基地周辺の湖水やスノウドリフトおよび海氷上の氷山を利用して生活水を確保してきた．これらの水源は気候条件などに左右されるとともに，その確保には多くの労働力と熱エネルギーを必要とした．また，造水熱源としては，エンジン発電機の廃熱を効率よく利用してきたが，屋外貯水槽や屋外配管の維持には多大な熱量を必要とした． 造水に関するこれまでの問題点を整理することにより，将来の造水法として，逆浸透膜を使った海水の淡水化法を提案する．これにより，少ないエネルギーで安定した生活水の確保が可能になると考えられる． The Japanese Antarctic Research Expedition (JARE) has sourced domestic water for daily use from ponds, snow drifts, and icebergs on sea ice at Syowa Station since the first wintering expedition. These water sources are dependent on weather conditions and maintenance of the sources requires considerable human effort and thermal energy. For example, the maintenance of outside water tanks and pipelines requires a lot of working force of wintering members and huge thermal energy which has been obtained from waste heat of engine generators. Here, we propose seawater desalination method using a reverse osmosis membrane to provide a reliable domestic water source to Syowa Station. Such a system could meet the station＇s water needs without requiring a large amount of staff time or heat energy. Errata | http://id.nii.ac.jp/1291/00010898/ departmental bulletin paper